Gene Therapy Principles and Challenges - Hashad, Doaa (IntechOpen, 2015)
Gene therapy is becoming a promising technology for the management of many human diseases. Hereditary and acquired disorders can both be tackled using the technique of gene therapy. This book provides detailed, up-to-date topics addressing basic principles of gene therapy and discussing some of the challenges encountered by scientists in developing this relatively novel technology. The development of new and efficient gene transfer vectors is of utmost importance in the progress of the field of gene therapy. Both viral and non-viral vectors are extensively discussed. A detailed chapter elaborates the problem of host immune rejection of transplanted donor cells or engineered tissue that can be avoided using the encapsulation of transgenic cells, thus avoiding the use of drugs that achieve immunosuppression.